Istanbul Taksim Republic Monument as an example of public art - Erarslan, Alev (Street Art & Urban Creativity, 2023)
Statues erected in public spaces are important elements of city squares and also represent traces of culture that are transferred into the future. These monuments are sometimes built for purposes of propaganda and at other times to commemorate a particular event, but whatever the reason for their creation, they are significant structures that serve as points of social interaction within the communities of which they are a part. When their relationship with the environment is firmly established, these monuments also assume an urban identity. The founder of modern Turkey, Mustafa Kemal Atatürk, wished to have the establishment of the new political model and the “nation state” emerging with the proclamation of the Republic (29 October 1923) symbolized through the language of architecture. Thus, as he promoted the slogan of “reaching the level of contemporary civilization,” he expected to have this concept reflected in architecture as much as possible in the physical sense during the Republican period of institutionalization. Part of his plan to achieve this was to create and activate public spaces in the urban landscape. This led to the monumentalization of the art of sculpture and to the appearance of the city squares of modern Turkey, where the statues that were the works of art displayed in these public spaces came to represent Atatürk and the newly established social order. This article aims to analyze how one of the symbols of Turkish architecture and of the Republican Period, the Taksim Republic Monument in Taksim Square, Istanbul, took shape as a public monument, and attempts at the same time to describe its social relationship with the surrounding environment.